The Teaching of Ethics and the Moral Competence of Medical and Nursing Students - Martins, Vera Silvia Meireles; Santos, Cristina Maria Nogueira Costa; Bataglia, Patricia Unger Raphael [UNESP]; Duarte, Ivone Maria Resende Figueiredo (Springer, 2020)
In a time marked by the development of innovative treatments in healthcare and the need for health professionals to deal with resulting ethical dilemmas in clinical practice, this study was developed to determine the influence of the bioethics teaching on the moral competence of medical and nursing students. The authors conduct a longitudinal study using the Moral Competence Test extended version before and after attending the ethics curricular unit, in three nursing schools and three medical schools of Portugal. In this questionnaire the participant is confronted with three ethical dilemmas (related to theft, euthanasia and the torture of a terrorist) and asked to evaluate arguments for and against the attitude of the main character (Worker, doctor and judge). For both nursing and medical students, C-score was lower after the attendance of the ethics curricular units, with a statistically significant decrease in the total score (from 21 to 19.5 on average;p = 0.046) for nursing students and a decrease not statistically significant for medical students (from 23.2 to 22 on average;p = 0.358). A multivariate analysis did not find any association between this decrease and gender, course, or age. The phenomenon of moral segmentation was observed, with better performance in the worker and judge dilemma, than in the doctor dilemma. These results highlight the need to reflect on the curricular strategies that can be implemented for health professionals to better develop moral competence and decision-making, allowing for the provision of humanized health care.
Keywords: Ethics education; Teaching; Moral development; Medical students; Nursing students